1. X^2-12x+20=0
D=144-4*1*20=144+80=224
x1=12+√2242 = 12+4√142 = 2(6+2√14)2=6+2√14
X2=12-√2242 = 12-4√142 = 2(6-2√14)2=6-2√14
2. X^2+10x+24=0
D=100-4*1*24=4
x1=-10+22 =-4
x2=-10-22 =-6
3. X^2+10x-24=0
D=100-4*1*(-24)=196
x1=-10+142 =2
x2=-10-142 =-12
1. X^2-12x+20=0
D=144-4*1*20=144+80=224
x1=12+√2242 = 12+4√142 = 2(6+2√14)2=6+2√14
X2=12-√2242 = 12-4√142 = 2(6-2√14)2=6-2√14
2. X^2+10x+24=0
D=100-4*1*24=4
x1=-10+22 =-4
x2=-10-22 =-6
3. X^2+10x-24=0
D=100-4*1*(-24)=196
x1=-10+142 =2
x2=-10-142 =-12